Chromitite mineralization in ultramafics of the kamchatsky mys peninsula (e. Kamchatka) - Osipenko, A.B.; Novakov, R.M. (Ofioliti, 2003)
Peculiarities of chemical compositions of the rock-forming minerals (Cr-spinels, first of all) have been studied for the ultramafics of the Kamchatsky Mys (cape) peninsula, Eastern Kamchatka. Obtained data, as well as isotope-geochemical dating and geochemical modeling previously carried out, allow us to distinguish three series of these rocks. The first one - abyssal peridotites originated from low depleted mantle restites (type I); type II - suprasubduction zone (SSZ) harzburgites originated from highly depleted mantle restites; type III - dunite-pyroxenite series of cumulate rocks. The latter originated from arc melts of boninite and, partly, tholeiite composition and they are just associated with chromite ores. Several stages in the Kamchatsky Mys ultramafite complex development are apparent; they correspond to different geodynamic regimes during the ophiolite formation. Each of these stages is characterized by its own type of Cr-spinel mineralization. The mere chromite ores are located in the inner parts of lens-shaped dunite bodies; they formed through interaction between host harzburgites and primitive arc melts.